Mangrove Ecotourism Development to Improve Coastal Community’s Welfare in Sedari Village, Karawang Regency, West Java - Bunga, Venny Ulya (Jurnal Abdimas Pariwisata, 2024)
Coastal regions in Indonesia grapple with high poverty rates. The prosperity of coastal communities hinges on the utilization of coastal natural resources. Mangroves, flourishing in these areas, play diverse roles in supporting the well-being of coastal communities, as illustrated comprehensively through their ecological and economic functions. A concrete implementation of this is the development of mangrove ecotourism, contributing to the economic and social value of the community. This article aims to explore the role and potential of mangrove forest ecotourism development in enhancing the well-being of Sedari Village’s communities. The methodology involves a literature review and structured interviews with key informants. The analysis shows that mangrove ecotourism in Sedari Village can contribute to: 1) a increasing Sedari Village’s income, potentially exceeding Rp. 100,000,000 annually, 2) Enlarging job opportunities for reducing the communities' reliance on sea catches, and 3) Improving the social and environmental value with active  participation in managing the mangrove forest ecotourism area.